Paleoenvironmental Evolution and Human Activities at the Hejia Site on the Ningshao Coastal Plain in Eastern China - Li, Haiyan; Sun, Jue; Ma, Chunmei; Zhao, Dongsheng; Li, Yongning; Ding, Fengya; Sun, Jia; Huang, Zhenhui; Shang, Guangchun; Deng, Yunkai (Frontiers in Earth Science, 2021)
The eastern China coastal plain is an ideal area for studying the human-environment interaction during the Neolithic period as there are multiple Neolithic sites in this area. Located in the Ningshao Coastal Plain of the south bank of Hangzhou Bay in eastern China, the Hejia Site is part of the late Hemudu Culture sites and includes the late Hemudu Culture, the Liangzhu Culture, and the Qianshanyang Culture. Based on palynology, charcoal, X-ray fluorescence (XRF), and magnetic susceptibility (χ), combined with accelerator mass spectrometry 14C dating and analysis of the archaeological cultural layers, we explored the paleoenvironmental evolution and human activities at the Hejia Site. (1) Pollen records suggest that the vegetation type was evergreen and deciduous broad-leaved mixed forest during the Middle Holocene. Cr/Cu and low-frequency magnetic susceptibility (χlf) reveal that the climate underwent through warm and wet (Hemudu Culture Period IV) –cool and dry (Liangzhu Culture Period) –warm and wet (Qianshanyang Culture Period) periods. (2) During the Middle Holocene, the intensity of human activities, related to the transformation of the natural environment, increased obviously. The increased Poaceae pollen (>37 μm) indicates that the ability of prehistoric humans in managing crop fields gradually increased from the late Hemudu Culture Period to the Liangzhu Culture Period. The charcoal concentration results suggest that the occurrence of high-intensity fire events during the late Hemudu Culture Period might be caused by the slash-and-burn operation, while those that occurred during the middle Liangzhu Culture Period might be caused by the increased fire demand owing to the greater ancestors’ lives and production activities in the Liangzhu Culture Period.